Photochemical and photobiological properties of furocoumarins and homologues drugs - F. Bordin (International Journal of Photoenergy)
Furocoumarins are natural photosensitizing drugs used in PUVA photochemotherapy and in photopheresis. Their therapeutic effectiveness is connected to the lesions they induce to various cell components, membranes, ribosomes, mitochondria, and in particular to DNA, damaged by formation of monofunctional adducts and of inter-strand cross-links (ISC). ISC represent a severe damage, mainly correlated to the main side effects observed in photochemotherapy, skin phototoxicity and genotoxicity. Searching for new monofunctional derivatives, two tetramethylfuroquinolinones, 1,4,6,8-tetramethyl-2H-furo[2,3-h]quinolin-2- one (FQ) and 4,6,8,9-tetramethyl-2H-furo[2,3-h]-quinolin-2-one (HFQ) were studied. Both compounds are very active; however while FQ produced many chromosomal aberrations and strong skin erythemas, HFQ practically did not induce such side effects. FQ and HFQ formed high levels of monoadducts but no ISC in DNA, but both provoked many DNA-protein cross-links (DPC). FQ induced these lesions by a biphotonic reaction: at first a furan-side monoadduct is formed, which is then converted into a DPC; thus the FQ molecule seemed to form the bridge between DNA and proteins. HFQ formed DPC by a single step (DPC at zero length, like UVC). For these features, HFQ appears to be the first molecule belonging to a new class of active but not phototoxic drugs for photomedicine.